Effect of Size of Polythene Bags on Seedling Growth and Budding Success in Jamun (Indian Journal of Arid Horticulture, 2025)
Studies were conducted to determine the effects of polythene bag size on seedling and root growth, and their impact on budding success in jamun at the experimental farm of CHES, Vejalpur, Godhra, Gujarat. Four sizes of polythene bags (25x15 cm, 25x10 cm, 30x8 cm, and 20x8 cm) were used, with a potting medium consisting of sand, soil, and FYM in a 1:1:1 ratio. Overall growth of jamun seedlings, after 8 months of seed sowing, in terms of seedling height, collar diameter, number of leaves per plant, budgable root stock percentage, root length, root diameter, and number of secondary and tertiary roots, was best in the 25x15 cm size polythene bags, followed by the 25x10 cm bags. Good quality seedling root stocks for budding purposes, with seedling height above 80 cm and collar diameter above 2.0 cm, along with a higher number of secondary and tertiary roots, were observed after 8 months in the 25x15 cm bags. Most of the quality seedling root stock parameters were also produced by the 25x10 cm polythene bags. The highest budding success percentage was recorded in the 25x15 cm size, followed by the 25x10 cm polythene bags. These findings suggest the use of 25x15 cm polythene bags for speedy seedling root stock growth and high budding success in jamun.
Keywords: Budding success; polythene bags; seedling growth; Syzygium cumini.